Exploring the mechanism of the anti-hypertension properties of Morinda citrifolia through a bioinformatics approach - Purwaningroom, Dian Laila; Maghfirah, Sholihatul; Rifai, Muhaimin; Widodo, Nashi (Kuwait Journal of Science, 2021)
Traditionally, noni (Morinda citrifolia L.) has been used as a treatment for hypertension in tropical countries. Many have proven that noni extract reduces blood pressure and is relatively safe (non-toxic) to the liver and kidney in lab animals. This extract is an angiotensin converting enzyme (ACE) inhibitor and plays a pivotal role in controlling blood pressure. However, researchers have yet to be able to identify the active compound that functions as the ACE inhibitor. Therefore, the objective of this study was to identify the active compound that acts as the ACE inhibitor as well as other anti-hypertension mechanisms using a bioinformaticsapproach. An enzyme activity analysis showed that noni methanol extract blocked ACE activity based on a comparable dosage (dose-dependent) with commercially anti-hypertension drugs. STITC and the STRINGdb database were used to identify the interaction between the M. citrifolia active compound with proteins target, revealing three active compounds, namely linoleic acid, palmitate and oleic acid, which were bound to PPARA protein, and NOS3, which is predicted as a regulator of blood pressure through the PPARA pathway. The findings showed that M. citrifolia has numerous active compounds containing multiple protein targets. However, in vitro and in vivo research should be conducted to provide evidence for the mechanism.